Some micro-evidence on the "Porter Hypothesis" from Austrian VOC emission standards - Thomas Roediger-Schluga (European Regional Science Association (ERSA), 2002)
In the context of the discussion on the 'Porter Hypothesis', a sizeable amount of research has been devoted to empirical tests of the impact of environmental regulation on both competitiveness and innovation. The standard practice is to regress some measure of regulatory stringency on some measure of competitiveness and innovation across several industries and/or countries. However, possibly due to measurement problems, the results of these studies tend to be inconclusive and if any effects are found, these are usually rather small. Addressing the measurement problem, this paper uses highly disaggregated foreign trade data and data from a full survey of the Austrian paint, coatings, printing inks and adhesive industry to examine the impact of Austrian VOC emission standards on Austrian manufacturers of the regulated products. These standards are particularly interesting in that they are the most restrictive of their kind in the world and therefore an excellent case to study some of the issues raised by the 'Porter Hypothesis'. Based on various measures of RCA, I find no impact (i.e. neither negative nor positive) on competitiveness, which is also supported by the industry's own evaluation in the survey. I do find, however, that the regulations restricted imports. An important corollary of this finding is that the industry's current attempt to have the more restrictive Austrian regulation relaxed to the more lenient provisions of the European VOC directive may be counterproductive, since contrary to popular belief this may increase import competition rather than facilitate exports. Second, I consider various indicators of innovation based on evidence from the survey. I find that the regulation induced sizeable changes of firms' product range which vary by technological sub-segment. These changes are also reflected in a more dynamic technological environment. R&D spending to develop compliant products is found to be very unevenly distributed. While some firms spent virtually nothing, other firms devoted almost their complete R&D budget to compliance innovations. This result is mainly a function of technology and to a lesser extent of organisational factors. Moreover, there is evidence that the introduction of compliant products displaced or postponed existing R&D projects, again with substantial variations by technology. Finally, the survey produces evidence that compliance efforts yielded new ideas and allowed some firms to acquire new competencies and technologies, which they would not have acquired in the absence of the regulation. However, the latter finding is most probably due to technologically backward (small) firms catching up. To summarise, the survey evidence reveals considerable heterogeneity in how firms were affected and responded to the regulation. Partly, this is an expected result of a uniform command-and-control regulation, partly it indicates a differential ability of firms to adapt to an external shock. Although based on a very small sample, the paper points to interesting lines of enquiry that should be explored in future research.
Keywords: 330